A Long-Standing Problem: A Review on the Solid Waste Management in the Philippines - Ericson E. Coracero; RB J. Gallego; Kristine Joy M. Frago; Ruel Joseph R. Gonzales (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
Solid waste management is considered a pressing global issue calling for an immediate response from the government and its people. The Philippines has a continuously rising amount of waste and is expected to further increase in the succeeding years. As reviewed, associated problems with solid waste management in the country include an increasing amount of solid waste, weak law implementation, scarcity of sanitary landfills, and improper disposal. The ultimate solution existing in the country is the RA 9003 or the Ecological Solid Waste Management Act of 2000 which highlights the practices of segregation, proper disposal, and waste diversion. The importance of envisioning a trash-free Philippines and encouraging people’s participation and awareness is also emphasized. Another possible solution to solid waste management is valorization which can also address other environmental problems such as the depletion of natural resources. These solutions enumerated will only be possible with the presence of good governance, active participation of the people of the country, and the cooperation of all constituents and agencies in the Philippines.